Reducing Coffee Acidity and Caffeine through the Roasting Method using Azadirachtaindica Firewood - Putera, Dwi; Yamin, Yamin; Firdaus, Thoriqi (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Coffee is known as an acidic drink, so it will make the stomach feel unpleasant. This research compares the roasting method with Azadirachta Indica firewood with machine and manual roasting processes. Each roasting method uses four maturity levels: light roast, medium roast, dark roast, and extra dark roast. The acidity test used a pH meter instrument, and the caffeine test used the spectrophotometric method, which was carried out at the Sucofindo Indonesia laboratory. The one-way ANOVA test analyzed each method’s acidity and caffeine results statistically. It can be seen that the sig < 0.05 in one-way ANOVA results for pH (0.006) and caffeine (0.013) coffee tests. So, there are significant differences in the three coffee roasting methods in reducing acidity and caffeine levels at each coffee roasting level. The average results of coffee acidity using the Azadirachta Indica wood roasting method (5.6), machine roasting (5.1), and manual roasting (4.8). The average yield of coffee caffeine with the Azadirachta Indica wood roasting method (2.13), machine roasting (2.55), and manual roasting (2.90). The roasting way using Azadirachta Indica firewood is the most effective, and there is a significant difference in reducing the acidity and caffeine of coffee at each level of coffee roasting. 55), and manual roasting (2.90). The most effective method of roasting is with Azadirachta Indica firewood, and there are significant differences in reducing the acidity and caffeine of coffee at each coffee roasting level. 55), and manual roasting (2.90). The most effective method of roasting is with Azadirachta Indica firewood, and there are significant differences in reducing the acidity and caffeine of coffee at each coffee roasting level.